A Hydrogen‐Bonded Organic‐Framework‐Derived Mesoporous N‐Doped Carbon for Efficient Electroreduction of Oxygen. Issue 7 (17th May 2016) - Liu, Ji; Li, Ligui; Niu, Wenhan; Wang, Nan; Zhao, Dengke; Zeng, Shuaibo; Chen, Shaowei
Abstract: Direct carbonization methods represent a facile strategy for the synthesis of functional carbon electrocatalysts, however, the resulting carbons are mostly microporous and of low surface area, which disfavor mass transfer, and usually have low electrocatalytic activity. In this study, a hydrogen‐bonded organic framework (HOF) comprising of melamine and trimesic acid is used as a highly porous precursor to prepare N‐doped carbons through facile, direct pyrolysis. The high nitrogen content of melamine and the intrinsically porous nature of the HOF facilitates the formation of a mesoporous carbon with 4.8 atom % content of nitrogen dopants and a significantly high surface area of 1321 m 2 g −1 . Electrochemical measurements show that the best sample, which was pyrolyzed at 800 °C (HOF‐800), exhibited efficient catalytic activity for oxygen electroreduction in 0.1 m KOH aqueous solution. This catalyst exhibits a much more positive onset potential, higher diffusion‐limited current density, higher electron‐transfer number in the low overpotential region, higher stability, and stronger tolerance against methanol crossover than the state‐of‐the‐art Pt/C catalysts. The results in this study suggest the potential of intrinsically porous HOFs for the development of highly efficient nonprecious‐metal electrocatalysts. Abstract : A new role for the HOF : A hydrogen‐bonded organic framework (HOF) comprising of melamine and trimesic acid is used as a highly porous precursor to prepare N‐doped carbons by a facile, direct pyrolysis. The resulting mesoporous carbon HOF‐800 has a high surface area of 1321 m 2 g −1 and efficiently catalyzes oxygen electroreduction in alkaline electrolyte.